APLIKASI UJIAN ONLINE BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER DI SMK PLUS PERTIWI - hanif rahmat; Fanji Fakhru Zaman; Enok Sri Hartini (Jurnal Fakultas Teknik Kuningan, 2022)
Implementing exams in education is very important to measure students' abilities and success during the teaching and learning process. As for the continued development of technology in the implementation of academic activities, speed and accuracy in data processing are required. SMK Plus Pertiwi has implemented an online-based exam system until this thesis was made using Google Form and there are still some obstacles. Therefore, it is necessary to make alternative systems for administering other exams that are more effective and efficient. This study aims to implement the CodeIgniter framework on a web-based online exam system so that SMK Plus Pertiwi can organize the exam process to process test scores. The research methodology uses qualitative methods and data is collected using interviews, observations and literature studies.. The research was conducted using the Waterfall model with the stages of Requirements Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System, and Operation and Maintenance. The programming language used in this application is PHP using MYSQL as the database.